Identifikasi Literasi Sains sebagai Landasan Pengembangan Media Pembelajaran berbasis AI pada Program Studi PGSD - M. Misbachul Huda; Atika Maulidina Hs (STKIP AL HIKMAH SURABAYA, 2025)
The challenges of 21st-century education demand a fundamental transformation in how prospective elementary school teachers understand and teach science. This study aims to identify the scientific literacy profile of elementary school teacher education (PGSD) students at STKIP Al Hikmah Surabaya as a baseline for developing AI-assisted learning media. The research employed a descriptive quantitative method with a survey design involving 68 students selected through purposive sampling. Data were collected using a standardized two-tier multiple-choice test adapted from PISA 2018 and TOSLS frameworks, covering content, process, and context dimensions. The results indicated that the majority of students (70.59%) reached the